Implementasi Perencanaan Kurikulum Baca Tulis dan Hafal Al-Qur’an pada Sekolah Dasar Islam Terpadu Wahdah Islamiyah 01 Makassar - Nasaruddin Nasaruddin; Siti Azisah; Arifuddin Siraj (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the application of curriculum management to learning to Read, Write and Memorize the Qur'an (BTHQ) at the Integrated Islamic Elementary School (SDIT) Wahdah Islamiyah 01 Makassar, especially at the planning stage. This research is a field research with a type of qualitative descriptive research and a case study and pedagogical approach. This study also uses Source Triangulation, Method Triangulation, and Theory Triangulation in testing the validity of the data. The results showed that SDIT Wahdah Islamiyah 01 Makassar had planned the BTHQ curriculum well. In its implementation, BTHQ curriculum planning includes determining the school's internal educational calendar, preparing SYLLABUS, preparing PROTA, preparing PROSEM, determining KKM, and making lesson plans. BTHQ curriculum planning is carried out at the beginning of each new school year using a grassroots approach through meetings with the Principal, Deputy Principal (Wakasek) of the Curriculum Section, the Academic Section, the Curriculum Team, the BTHQ Quality Assurance Team, and all BTHQ teachers. The obstacle faced was the difference in perception between BTHQ teachers about the goals and the BTHQ curriculum itself in planning. School administrators overcome this by holding coordination meetings, polling, discussing and strengthening their respective roles. Periodic activities, teacher management training from schools, BTHQ internal teacher coaching, and periodic training from the Wahdah Islamiyah Center are the supporting forces in the success of the BTHQ curriculum planning process at the beginning of each school year.